PENINGKATAN MOTIVASI BELAJAR GERAK DASAR LARI MELALUI PENDEKATAN BERMAIN DALAM PEMBELAJARAN PENJAS SISWA KELAS V SD I DONOTIRTO KRETEK BANTUL - Aris Priyanto (Jurnal Pendidikan Jasmani Indonesia, 2013)
This study aims to improve the learning motivation for the basic running movements in the learning of physicaleducation through the game approach. This was a classroom action research study involving Grade V students ofSD I Donotirto. The study was conducted in cycles, each of which consisted of 1 meeting. The data on motivationwere collected through interviews, observations, and documentation. They were analyzed by means of the qualitativedescriptive technique. The results of the study showed that the learning through the game approach improved thestudents’ learning motivation for the basic running movements so that they were capable of improving the average50-meter-running speed by 9.75 (in the good category) in Cycle I and 9.46 (in the good category) in Cycle II. Thenumber of the students who attained the mastery in Cycle I was 23 students (67.65%) and that in Cycle II was 29students (85.29%); this was above the individual mastery with the good category and the classical mastery of 75%.Keywords: learning motivation, game approach, basic running movements